A New GPS-based evaluation of distortions in the Australian Height Datum in Western Australia - Featherstone, Will; Filmer, Michael (Royal Society of Western Australia, 2008)
Previous work on assessing the errors in the Australian Height Datum (AHD) across Western Australia used fewer and older global positioning system (GPS) data and a global quasigeoid model. A larger and improved State-wide set of 243 GPS-derived ellipsoidal heights and a regional gravimetric quasigeoid model are now available. Therefore, it is possible to re-evaluate the north-south tilt in the AHD and look for regional systematic distortions with some more confidence in Western Australia. This new analysis shows an apparent north-south tilt of ~0.27 mm/km in the existing AHD over the whole of the State, but which increases to ~0.6 mm/km over smaller regions, showing regional systematic distortions. When mean sea-level constraints are removed from the AHD by a minimally constrained least-squares adjustment of the spirit-levelling observations that is less prone to the effect of sea-surface topography, the north-south tilt reduces to ~0.18 mm/km, but the regional distortions remain, showing that errors are present in the spirit-levelling observations.